Circulating tumour DNA in patients with advanced melanoma treated with dabrafenib or dabrafenib plus trametinib: a clinical validation study. Issue 3 (March 2021) - Syeda, Mahrukh M; Wiggins, Jennifer M; Corless, Broderick C; Long, Georgina V; Flaherty, Keith T; Schadendorf, Dirk; Nathan, Paul D; Robert, Caroline; Ribas, Antoni; Davies, Michael A; Grob, Jean Jacques; Gasal, Eduard; et al.
Summary: Background: Melanoma lacks validated blood-based biomarkers for monitoring and predicting treatment efficacy. Cell-free circulating tumour DNA (ctDNA) is a promising biomarker; however, various detection methods have been used, and, to date, no large studies have examined the association between serial changes in ctDNA and survival after BRAF, MEK, or BRAF plus MEK inhibitor therapy. We aimed to evaluate whether baseline ctDNA concentrations and kinetics could predict survival outcomes. Methods: In this clinical validation study, we used analytically validated droplet digital PCR assays to measure BRAF V600 -mutant ctDNA in pretreatment and on-treatment plasma samples from patients aged 18 years or older enrolled in two clinical trials. COMBI-d (NCT01584648 ) was a double-blind, randomised phase 3 study of dabrafenib plus trametinib versus dabrafenib plus placebo in previously untreated patients with BRAF V600 mutation-positive unresectable or metastatic melanoma. Patients had an Eastern Cooperative Oncology Group (ECOG) performance status of 0 or 1. COMBI-MB (NCT02039947 ) was an open-label, non-randomised, phase 2 study evaluating dabrafenib plus trametinib in patients with BRAF V600 mutation-positive metastatic melanoma and brain metastases. Patients in cohort A of COMBI-MB had asymptomatic brain metastases, no previous local brain-directed therapy, and an ECOG performance status of 0 or 1. Biomarker analysis was a prespecified exploratory endpoint in both trials and performed in the intention-to-treat populations in COMBI-d and COMBI-MB. We investigated the association between mutant copy number (baseline or week 4 or zero conversion status) and efficacy endpoints (progression-free survival, overall survival, and best overall response). We used Cox models, Kaplan-Meier plots, and log-rank tests to explore the association of pretreatment ctDNA concentrations with progression-free survival and overall survival. The effect of additional prognostic variables such as lactate dehydrogenase was also investigated in addition to the mutant copy number. Findings: In COMBI-d, pretreatment plasma samples were available from 345 (82%) of 423 patients and on-treatment (week 4) plasma samples were available from 224 (53%) of 423 patients. In cohort A of COMBI-MB, pretreatment and on-treatment samples were available from 38 (50%) of 76 patients with intracranial and extracranial metastatic melanoma. ctDNA was detected in pretreatment samples from 320 (93%) of 345 patients (COMBI-d) and 34 (89%) of 38 patients (COMBI-MB). When assessed as a continuous variable, elevated baseline BRAF V600 mutation-positive ctDNA concentration was associated with worse overall survival outcome (hazard ratio [HR] 1·13 [95% CI 1·09–1·18], p<0·0001 by univariate analysis), independent of treatment group and baseline lactate dehydrogenase concentrations (1·08 [1·03–1·13], p=0·0020), in COMBI-d. A ctDNA cutoff point of 64 copies per mL of plasma stratified patients enrolled in COMBI-d as high risk or low risk with respect to survival outcomes (HR 1·74 [95% CI 1·37–2·21], p<0·0001 for progression-free survival; 2·23 [1·73–2·87], p<0·0001 for overall survival) and was validated in the COMBI-MB cohort (3·20 [1·39–7·34], p=0·0047 for progression-free survival; 2·94 [1·18–7·32], p=0·016 for overall survival). In COMBI-d, undetectable ctDNA at week 4 was significantly associated with extended progression-free and overall survival, particularly in patients with elevated lactate dehydrogenase concentrations (HR 1·99 [95% CI 1·08–3·64], p=0·027 for progression-free survival; 2·38 [1·24–4·54], p=0·0089 for overall survival). Interpretation: Pretreatment and on-treatment BRAF V600 -mutant ctDNA measurements could serve as independent, predictive biomarkers of clinical outcome with targeted therapy. Funding: Novartis.